Elucidating the Key Structural Features of Carbohydrates and Surfactants Necessary for Inhibiting Ice Recrystallization - Balcerzak, Anna (Université d'Ottawa / University of Ottawa, 2014)
Ice recrystallization during thawing after cryopreservation results in extensive cellular damage that ultimately leads to cell death and decreased cell viabilities. This is a significant problem particularly with cryopreserved cells utilized in various regenerative medicine therapies. Given the success of these therapies to treat spinal cord injury, cartilage lesions, and cardiacdisease, the development of new and improved cryprotectants that minimize cell damageduring freeze-thawing and improve cell viability post-cryopreservation are urgently required. The current cryopreservative dimethyl sulfoxide, DMSO, is associated with cytotoxicity in clinical settings and is not an optimal cryopreservative. Our laboratory is interested in synthesizing small molecules that possess the property of ice recrystallization inhibition (IRI) activity that can be utilized as cryopreservatives without the cytotoxic effects associated with DMSO. This thesis focuses on the development of small molecule ice recrystallization inhibitors and elucidating the structural features of disaccharides and surfactants that are responsible for potent IRI activity. The first part of this study examines simple disaccharide derivatives mimicking those found in the native AFGP to determine whether disaccharide structure influences IRI activity. Towards this end, the (1,6)-linked AFGP disaccharide analogue was synthesized, assessed for IRI activity using a splat-cooling assay, and compared to the native (1,3)- and (1,4)-linked AFGP disaccharide analogues. The change in linkage was found to have a profound affect on IRI activity. The second part of the study focuses on surfactants and gelators as ice recrystallization inhibitors. Our laboratory has demonstrated that carbohydrate-based hydrogelators can be potent inhibitors of ice recrystallization. While our studies have indicated that a delicate balance between hydrophobic and hydrophilic interactions is crucial for ice recrystallization inhibition (IRI) activity, the essential structural features necessary for potent IRI activity remain unknown. To address this issue, structurally diverse amino acid-based surfactants/gelators, anti-ice nucleating agents, and glycoconjugates were synthesized and assessed for IRI activity. The results indicate that long alkyl chains and increased hydrophobicity are important for potent IRI activity and iii that the position of these alkyl chains is essential. Also, the counterion of these compounds affects the IRI activity and is related to the counterion degree of hydration. These compounds were assessed for their ability to cryopreserve human liver cells (Hep G2) and human bone marrow cells (Tf-1α) in cell-based assays. Additionally, the best IRI assay solution was determined, which involved studying how the salts of the phosphate buffered saline (PBS) solution modulated IRI activity. Finally, small molecule ice recrystallization inhibitors were assessed for their ability to protect the viral vectors vaccinia virus, vesicular stomatitis virus, and herpes simplex-1 virus at various storage conditions. This will aid in developing improved preservation protocols for vaccines and viruses utilized in cancer therapy (oncolytic viruses).
Keywords: ice recrystallization inhibition; cryopreservation